Dying Hungry: Nazi Ideology and the Pragmatism behind Starvation in Implementing the Final Solution - Feferman, Kiril (East/West, 2021)
German theories and policies regarding the relationship between food and Jewish citizens of eastern Europe served as an important foundation of the Nazis’ Judenpolitik during the Holocaust (1933-45). The mass starvation of Jews in German-dominated Europe was the result of a carefully calculated policy to make the Jews pay for a long list of misfortunes they had allegedly inflicted on the Germans. This policy evolved from a highly restrictive and discriminatory approach toward German Jews, which unfolded against a backdrop of harsh food policies applied to the local non-Jewish population.